Alfabetización en salud sobre calidad de vida en pacientes pediátricos con cáncer: módulos sobre cuidados paliativos pediátricos - Garcia-Quintero, X (2023)
Objective. To describe the development of educational materials for parents and other caregivers of children with cancer, which utilized a culturally sensitive approach to reduce acceptance barriers to palliative care (PC). Methods. The Pan American Health Organization (PAHO), St. Jude Children’s Research Hospital, and partners in Latin America and the Caribbean collaborated in a three-phase project, beginning with a needs assessment survey of caregivers of children with cancer in Peru. Based on this finding, an interdisciplinary team of pediatric PC experts developed educational content that was designed and validated by an international committee of PC and communication experts. Results. The collaboration resulted in the development of an eight-module series that introduces caregivers to key concepts of pediatric PC, including management of pain, quality of life, and end of life care. The series was designed to reduce caregiver stigma associated with PC through culturally sensitive education that addresses the low levels of health literacy among caregivers in Latin America and the Caribbean. In the 15 months since the launch, these modules have been distributed throughout Latin America and were downloaded 2 825 times. Conclusions. Educational materials and anticipatory guidance of PC were considered to be a priority for parents and other caregivers of children with cancer throughout Latin America. The materials developed through this project have been widely utilized and are available through the PAHO website and the Together by St. Jude™ online resource.